Simultaneous Determination of Sodium Benzoate Potassium Sorbate and Natamycin Content in Iranian Yoghurt Drink (Doogh) and the Associated Risk of Their Intake through Doogh Consumption - Zahra Esfandiari; Mohammad Badiey; Pooya Mahmoodian; Reza Sarhangpour; Elham Yazdani; Maryam Mirlohi (Tehran University of Medical Sciences, 2013)
Background: Regarding the public health concerns over the use of food preservatives in yoghurt drink "Doogh", the aim of this study was the determination of sodium benzoate, potassium sorbate and natamycin in Doogh. Based on Iranian national standard, none of these preservatives are permitted to be used in Doogh.Methods: A total of 39 Doogh samples were analyzed through RP- HPLC in order to quantify sodium benzoate, potassium sorbate and natamaycin simultaneously. Exposure to each preservative is estimated by mean and maximum concentrations as the residue levels. The per capita Doogh consumption was calculated by the published data from official reports for Doogh annual production in Iran.Results: All samples were shown to contain sodium benzoate while natamaycin was detected in 10.25% of the samples and potassium sorbate was not detected in any of them. Sodium benzoate concentration extremely varied among the investigated samples ranged from 0.94 to 9.77 mg/l. Due to the result of the exposure estimation, no serious public health concern would exist regarding the mentioned preservatives.Conclusions: The detection of sodium benzoate in all Doogh samples could indicate the natural production of benzoic acid in yoghurt. Sodium benzoate may be formed through the interaction of the added food grade salt to the Doogh formula which contains benzoic acid. The results of exposure estimation show the lack of health risk within the usage of preservatives in spite of the national regulatory agencies does not permit the preservative use.